Evaluating the efficacy and safety of simple combination of analgesics with and without low dose opioid for perioperative analgesia, hemodynamic and recovery profile in various surgeries posted under general anaesthesia: a prospective randomised controlled study - Shaik Ayesha; Aruna Kumari S.; Jareena; K. Lakshmana Rao (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Multimodal analgesia is an emerging technique.It has been consistently demonstrated to minimise opioid consumption, related side effects and vital component of enhanced recovery after surgery pathways. The current study presents use of combination of readily available medication as a part of multimodal analgesia. Balanced anaesthesia with multimodal analgesia is harmonious use of combination of agents to produce desired effects with minimal side effects of individual agents. Methods: This study was done in a tertiary health care centre, Government General Hospital, Kakinada over a duration of two months from August 2022 to September 2022. 60 adult patients of either sex of physical status ASA grade 1and 2 undergoing elective surgery under general anaesthesia were randomly allocated into Group A and Group B of 30 patients. Group 1: received Inj. Lignocaine+Inj. Paracetamol+Inj. Magnesium sulphate+Inj. Fentanyl. Group 2:received Inj. Lignocaine+Inj. Paracetamol+Inj. Magnesium sulphate+Normal saline (control group) as premedication for perioperative analgesia. Results: All patients were hemodynamically stable for first 30 minutes period of observation in Group A compared to Group B. There is clinically and statistically significant difference in the duration of analgesia in Group A compared to Group B. There is no statistically significant difference in the Numerical Rating Scale (NRS) for pain in both the groups. Conclusions: This study concluded that simple analgesia combination of multimodal analgesia regimen comprising of Inj. Lignocaine, Inj. Paracetamol and Inj. Magnesium sulphate produces safe and effective analgesia with good recovery profiles and no adverse opioid related side effects for ASA 1 and 2 patients posted under general anaesthesia.